Palmarès musicaux: où sont les femmes? - Vallet, Stéphanie (La Presse, 2019)

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies